2015
DOI: 10.3390/ijms160510185
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Lung Cancer Cells Grown as Multicellular Tumour Spheroids to Zinc Sulfophthalocyanine Photosensitization

Abstract: Photodynamic therapy (PDT) is phototherapeutic modality used in the treatment of neoplastic and non-neoplastic diseases. The photochemical interaction of light, photosensitizer (PS) and molecular oxygen produces singlet oxygen which induces cell death. Zinc sulfophthalocyanine (ZnPcSmix) has been shown to be effective in A549 monolayers, multicellular tumor spheroids (MCTSs) (250 µm) and not on MCTSs with a size of 500 µm. A549 cells used in this study were grown as MCTSs to a size of 500 µm in order to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…This mode of PDT which is indicated for multicellular tumours has been explored previously in vitro. The efficacy of PDT concerning a monolayer as compared to multicellular spheroids indicated that spheroids are more resistant to PDT, however this can be overcome using a dose dependent manner of inducing cell death [68]. Although PDT has successfully been used to treat lung cancer a major pitfall still include low tumour selectivity, especially in a scenario where the lung cancer's genomics are predisposed to malignant metastatic tumours [42].…”
Section: Resultsmentioning
confidence: 99%
“…This mode of PDT which is indicated for multicellular tumours has been explored previously in vitro. The efficacy of PDT concerning a monolayer as compared to multicellular spheroids indicated that spheroids are more resistant to PDT, however this can be overcome using a dose dependent manner of inducing cell death [68]. Although PDT has successfully been used to treat lung cancer a major pitfall still include low tumour selectivity, especially in a scenario where the lung cancer's genomics are predisposed to malignant metastatic tumours [42].…”
Section: Resultsmentioning
confidence: 99%
“…31,32 ZnPcS-PDT also displays therapeutic efficacy in a similar manner within other cancer cell lines like human lungs (A549) and colon cancer cell (DLD-1). 33,34 The combination of DOX and ZnPcS-PDT was found to significantly decrease the viability and increase the cytotoxicity of cancer cells compared to the ZnPcS-PDT and DOX alone. CI analysis used to quantitatively evaluate the interactive effects of DOX and ZnPcS-PDT and combination showed a CI <1.…”
Section: Discussionmentioning
confidence: 99%
“…74 This is consistent with other MCS models that have demonstrated increased resistance of the 3D MCS model to pulmonary therapeutics relative to classic monoculture systems. 73,75 Recently, changes in migration, proliferation, and matrix remodeling have been observed using alveolar epithelial cells on microspheres encapsulated with a fibroblast hydrogel for a model of cancer progression and stromal-epithelial tumor microenvironment. 76 Spheroids have been utilized in a high-throughput 3D lung tumor assay to screen the effects of compounds on cellular proliferation and migration for small molecule therapeutic development; however, limited use of MCS models beyond drug discovery has been seen.…”
Section: Faber and Mcculloughmentioning
confidence: 99%